The Effect of Cloride Acid Concentration to The Phenolic Compound and The Antioxidant Activity in Methanol Extract of Sargassum oligocystum - Etik Wahyuningsih; Rachma Nurhayati; Astrid Kusuma Putri (Jurnal Ilmiah Sains, 2024)
Sargassum oligocystum is a species of brown algae that has many biological activities. The aim of this research is to analyze the polyphenol compound and antioxidant activity with methanol solvent at varying acid concentrations. Addition of hydrochloric acid in methanol solvent at various concentrations of 0.1 N; 0.2 N, 0.3 N in Sargassum oligocystum showed an increase in polyphenol compound, 2.82 mg GEA/g; 3.27 mg GEA/g and 3.88 mg GAE/g, respectively. The increase in polyphenol compound is proportional to the increase in antioxidant activity, 0.92 mg; 0.55 mg and 0.29 mg, respectively. The results showed that methanol extraction with variations of hydrochloric acid in Sargassum oligocystum contained polyphenols and antioxidant activity which increased with increasing acid concentration. Keywords: Antioxidant activity; cloride acid; methanolic extract; phenolic compound; Sargassum oligocystum